Kinetochore assembly and disassembly during mitotic entry and exit. (June 2018) - Hara, Masatoshi; Fukagawa, Tatsuo
Abstract : Faithful chromosome segregation during mitosis in eukaryotes requires a large protein complex, kinetochore, formed on the centromere of each chromosome, to attach to spindle microtubules. Among the kinetochore proteins, Constitutive Centromere-Associated Network (CCAN) and KMN-network proteins form the base of the vertebrate kinetochore architecture. The CCAN proteins constitutively localize to the centromere throughout the cell cycle, whereas KMN-network proteins are recruited to the CCAN only during mitosis. Recent studies in cellular and structural biology, as well as biochemical reconstitutions, have revealed that mitotic phosphorylation of kinetochore proteins has critical roles in kinetochore organization. Here, we discuss the molecular processes of kinetochore assembly during mitotic entry and its disassembly during mitotic exit.